Sex offender risk assessment, sources of variation, and the implications of misuse - Lanterman, Jennifer L. (Criminal justice and behavior, 2014)
The current study examines whether or not prosecutors in New Jersey are properly using the state?s sex offender risk assessment tool, and the implications of improper implementation. All prosecutors and public defenders who handle Megan?s Law cases in New Jersey participated in two confidential surveys. The results of those surveys were used to score a fact pattern. Results reveal that prosecutors are not consistently implementing risk assessment, that there are several sources of disparities, and that these disparities can result in a substantial variation in risk assessment scores. The implications of these disparities are that offender risk is often over-classified, thereby increasing offender supervision costs and potentially compromising public safety. The authors make recommendations for formal training on the proper use of risk assessment tools, as well as an assessment supervision plan. Although this research was conducted in New Jersey, the findings have implications for risk assessment tools employed by other jurisdictions.